IN VITRO COMPARATIVE STUDY OF DIFFERENT BRANDS OF PANTOPRAZOLE SODIUM ENTERIC COATED TABLETS MARKETED IN ADDIS ABABA, ETHIOPIA - Nigatu, Muluken; Mohammed, Fozia; Temesgen, Abrham (Asian Journal of Pharmaceutical Research and Development, 2019)
Pantoprazole is a substituted benzimidazole proton pump inhibitor used in treatment of patients with serious or refractory acid-related diseases. The objective of the present study was to undertake comparative in vitro evaluation of different brands of pantoprazole sodium tablets available in different retail outlets in Addis Ababa, Ethiopia. All brands were evaluated using established procedures to assess the pharmaceutical quality characteristics. The measured thickness of studied brand tablets was found to be in the range of 2.79 to 3.49 mm.Brand E (175.4 ± 3.73 N) exhibited maximum hardness while brand C (110.2 ± 6.43 N) had the lowest hardness. When the mean weights of the sample brands are compared,brandC had maximum weight (151.22mg) and brandD weighed the least (79.18 mg).The disintegration time test indicated that any of the pantoprazole sodium tablet brands did not disintegrate in 0.1N HClacidic medium for 2 hrs but all disintegrated in the time range of 12.43 min to 24.42 min in phosphate buffer.The in vitrodrug release study depicted that all brands of pantoprazole sodium tablets released not more than 10% of the labeled amount within 2 hrs under 0.1N HClmedium but showed similar drug release in the buffer medium ranging between 89 and 92% within 45 minutes.Therefore, the results of the present study revealed that all of the tested brands of the pantoprazole sodium enteric coated tablet fulfilled the criteria set in the official monograph for in vitro quality control tests.